Influence of preliminary introduction of placenta cryoextracts on ultrastructure of rat’s adrenal gland glomerular zone with acute renal failure. - L. M. Marchenko; T. P. Govorukha; M. V. Repin; V. I. Strona (Морфологія, 2018)
Background. When developing new available methods of restorative correction of renal function in renal insufficiency, the placenta preparations are increasingly used. The course of acute renal failure and its transformation into a chronic form significantly affects aldosterone, that is one of the links of the hypothalamic-pituitary-adrenal system. Determination of ultrastructural adrenocorticocyte changes in the glomerular zone of adrenal glands and the level of saturation of cells with lipids will allow judging the degree of this hormone secretion. The objective of the research was to investigate the ultrastructure of cells of adrenal cortex glomerular of rats with acute renal failure when introducing the placenta cryoextracts of allogeneic and xenogeneic origin prior to the renal pathology simulation. Methods. The research object were 65 white male rats aged 4 months. Animals were givenwith the cryoextracts of placental tissue of various origins by 0.5 ml three times a week. A week after the introduction of cryoextracts, renal insufficiency was modeled by intramuscular injection of 50% aqueous solution of glycerol in a dose of 10 ml per 1 kg body weight. Animals were divided into 3 groups: 1 - rats with the simulated renal failure; 2, 3 - rats with simulated renal failure, which were pre-administered with cryoexracts of the rat and human placenta, respectively. Animals were withdrawn from the experiment to the first, second and third week after the introduction of glycerol. The ultrastructure of the cells was examined using an electron microscope PEM-125K (Selmi JSC). Results. Within 3 weeks of glycerol model of an acute renal failure, regardless of the previous administration of either rat’s or human placenta cryoextracts the ultrastructure of adrenocorticocytes of glomerular zone showed the signs of strengthening steroidogenesis, which were manifested by hypertrophy of endoplasmic reticulum and mitochondria, swelling of mitochondria, formation of myelin-like structures and mitochondrial vacuoles as well as tight mitochondrial complexes, endoplasmic reticulum and liposomes. Conclusion. The signs of increased steroidogenesis in glomerular zone of rat’s adrenal cortex were most pronounced when introducing the xenogeneous cryoextracts of placenta prior to the start of pathology modeling.